Patient Outcomes Are Not Improved by Platelet-Rich Plasma Injection Onto the Capsule at the Time of Closure During Hip Arthroscopy for Femoroacetabular Impingement Syndrome - S. Craig Morris, M.D; William T. Haselman, B.S; Michael B. Banffy, M.D (Elsevier, 2023)
Purpose: To determine the effect of platelet-rich plasma (PRP) injection onto the capsule at time of closure on outcomes of patients undergoing hip arthroscopy for femoroacetabular impingement syndrome. Methods: Patients who underwent hip arthroscopy between January 2014 and December 2021 were retrospectively identified. The first cohort included patients who received PRP injection onto the capsule following capsular closure at the conclusion of the case. The second cohort did not receive PRP. Pain scores on a visual analog scale, Modified Harris Hip Scores, Single Assessment Numeric Evaluation (SANE), as well as Patient-Reported Outcomes Measurement Information System Physical Function scores were obtained preoperatively as well as at multiple time points postoperatively up to 2 years. Results: In total, 345 patients were included in the study, with 293 in the PRP cohort and 52 in the non-PRP cohort. There was no significance difference in age (P = .69), sex, or preoperative pain (P = .92) and patient-reported outcome scores between the 2 groups (modified Harris Hip Score, P = .38; Patient-Reported Outcomes Measurement Information System Physical Function, P = .48), except for preoperative SANE scores, which had a greater baseline in the PRP group (P < .001). Using both observed data as well as repeated measure analysis of variance model to estimate for missing data after baseline, we found there were no differences in visual analog scale pain scores nor patient-reported outcome scores at any time point. There was similarly no difference in change from baseline for SANE scores. There was no difference in rate of revision surgery between the 2 cohorts (P = .66). Conclusions: Based on the results of this study, intraoperative PRP injection onto the capsule at the time of capsular closure does not improve outcomes of patients undergoing hip arthroscopy for femoroacetabular impingement syndrome. Level of Evidence: Level III, retrospective comparative study.